Profiling Docetaxel in Plasma and Urine Samples from a Pediatric Cancer Patient Using Ultrasound-Assisted Dispersive Liquid-Liquid Microextraction Combined with LC-MS/MS - Olga Maliszewska; Anna Roszkowska; Marcin Lipiński; Natalia Treder; Ilona Olędzka; Piotr Kowalski; Tomasz Bączek; Ewa Bień; Małgorzata Anna Krawczyk; Alina Plenis (MDPI AG, 2023)
In recent years, therapeutic drug monitoring (TDM) has been applied in docetaxel (DOC)-based anticancer therapy to precisely control various pharmacokinetic parameters, including the concentration of DOC in biofluids (e.g., plasma or urine), its clearance, and its area under the curve (AUC). The ability to determine these values and to monitor DOC levels in biological samples depends on the availability of precise and accurate analytical methods that both enable fast and sensitive analysis and can be implemented in routine clinical practice. This paper presents a new method for isolating DOC from plasma and urine samples based on the coupling of microextraction and advanced liquid chromatography with tandem mass spectrometry (LC-MS/MS). In the proposed method, biological samples are prepared via ultrasound-assisted dispersive liquid-liquid microextraction (UA-DLLME) using ethanol (EtOH) and chloroform (Chl) as the desorption and extraction solvents, respectively. The proposed protocol was fully validated according to the Food and Drug Administration (FDA) and the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) requirements. The developed method was then applied to monitor the DOC profile in plasma and urine samples collected from a pediatric patient suffering from cardiac angiosarcoma (AS) with metastasis to lungs and mediastinal lymph nodes, who was receiving treatment with DOC at a dose of 30 mg/m2 body surface area. Due to the rarity of this disease, TDM was carried out to determine the exact levels of DOC at particular time points to ascertain which levels were conducive to maximizing the treatment's effectiveness while minimizing the drug's toxicity. To this end, the concentration-time profiles of DOC in the plasma and urine samples were determined, and the levels of DOC at specific time intervals up to 3 days after administration were measured. The results showed that DOC was present at higher concentrations in the plasma than in the urine samples, which is due to the fact that this drug is primarily metabolized in the liver and then eliminated with the bile. The obtained data provided information about the pharmacokinetic profile of DOC in pediatric patients with cardiac AS, which enabled the dose to be adjusted to achieve the optimal therapeutic regimen. The findings of this work demonstrate that the optimized method can be applied for the routine monitoring of DOC levels in plasma and urine samples as a part of pharmacotherapy in oncological patients.